Catalyst and preparation method thereof, membrane electrode and fuel cell

By developing Co/Cu-N-C catalysts, using the combination of carbon-nitrogen support and bimetallic catalytic particles, the problem of reverse polarity phenomenon of fuel cells under complex operating conditions is solved, and the electrochemical performance and safety performance are improved.

CN119495755APending Publication Date: 2025-02-21FAW JIEFANG AUTOMOTIVE CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411389206.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

Under complex operating conditions, the catalytic layer may not be able to provide enough protons and electrons due to insufficient fuel, which will cause water electrolysis or carbon corrosion reaction, resulting in an anode potential higher than the cathode, causing the 'reverse' phenomenon to occur, and severe damage. Catalytic layer and gas diffusion layer.

Method used

A Co/Cu-N-C catalyst consisting of a carbon-nitrogen support and a Co metal and Cu metal catalytic particles supported thereon, chemically polymerizing a cyclic amine compound with a cobalt and a copper source and performing a The catalyst is formed by pyrolysis and acid solution treatment.

Benefits of technology

The activity and utilization of the catalyst are improved, the cost is reduced, and the anti-reverse ability is enhanced, thereby improving the electrochemical performance and safety performance of fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119495755A_ABST
    Figure CN119495755A_ABST
Patent Text Reader

Abstract

The invention provides a catalyst and a preparation method thereof, a membrane electrode and a fuel cell. The catalyst comprises: a carbon-nitrogen carrier having a nanometer ordered pore structure; the catalyst comprises a carbon-nitrogen carrier and catalytic particles loaded on the carbon-nitrogen carrier, the catalytic particles comprise Co metal and Cu metal, and the catalytic particles and the carbon-nitrogen carrier form a Co / Cu-N-C catalyst. According to the catalyst provided by the invention, the carbon-nitrogen carrier has a nano ordered porous structure, so that active sites of the catalyst are fully exposed, the accessibility of an electrolyte is improved, the activity and the utilization rate of the catalyst are improved, non-noble metals Co metal and Cu metal are loaded on the inner and outer surfaces of the carbon-nitrogen carrier to serve as catalytic particles, bimetal active sites are provided, and the catalytic activity of the catalyst is improved. According to the present invention, the cost is reduced, the catalyst has high activity, the catalyst can catalyze the water electrolysis reaction when the catalyst is applied to the fuel cell, and the strong anti-polarity ability is provided so as to improve the electrochemical performance and the safety performance of the cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fuel cells, and in particular to a catalyst and a preparation method thereof, a membrane electrode, and a fuel cell. Background Art

[0002] Proton exchange membrane fuel cells have the characteristics of high energy conversion efficiency, fast start-up speed and zero emissions. They are one of the most promising power sources to replace traditional internal combustion engines in the field of transportation.

[0003] However, when the proton exchange membrane fuel cell is operating under complex operating conditions such as start-stop, rapid load change and low-temperature start-up, the catalyst layer may not be able to provide enough protons and electrons for the hydrogen oxidation reaction due to insufficient fuel. In order to maintain the charge balance in the catalyst layer, reactions such as water electrolysis or carbon corrosion will occur at this time, which will cause the anode potential to be higher than the cathode, the battery voltage to become negative, and the "reverse polarity" phenomenon to occur. Battery reverse polarity will seriously damage the catalyst layer and gas diffusion layer, thereby affecting battery performance and durability, and in severe cases, it will cause safety accidents.

[0004] In traditional technology, the occurrence of reverse polarity is prevented through system control strategies, but this system control strategy increases the complexity and cost of the battery system, and these strategies cannot fundamentally avoid the occurrence of reverse polarity. Other studies have conducted anti-reverse polarity research from the material aspect, such as introducing water electrolysis catalyst IrO2 into the catalyst layer, which has improved the anti-reverse polarity ability of the anode catalyst layer to a certain extent, but the activity and utilization rate of these catalysts are poor, and the preparation method is complicated and the cost is high. Summary of the invention

[0005] Based on this, it is necessary to provide a catalyst and its preparation method, a membrane electrode, and a fuel cell to improve the activity and utilization rate of the catalyst and reduce the cost of the catalyst. The preparation method is simple. The catalyst is applied to fuel cells to improve the battery's anti-reverse polarity ability, thereby improving the battery's electrochemical performance and safety performance.

[0006] The first aspect of the present application provides a catalyst, which includes: a carbon-nitrogen carrier having a nano-ordered pore structure; and catalytic particles loaded on the carbon-nitrogen carrier, the catalytic particles including Co metal and Cu metal, and the catalytic particles and the carbon-nitrogen carrier constitute a Co / Cu-NC catalyst.

[0007] The second aspect of the present application provides a method for preparing a catalyst, which comprises the following steps: S1, dispersing a cyclic amine compound and a cobalt source in a solvent, stirring and reacting to obtain a Co precursor; S2, dispersing the Co precursor and a copper source in a solvent, stirring and reacting to obtain a Co-Cu precursor; S3, pyrolyzing the Co-Cu precursor to form a powder; S4, adding an acid solution to the powder for treatment, and then purifying it to obtain a Co / Cu-NC catalyst.

[0008] In some embodiments, in step S1, the cyclic amine compound includes an amino group.

[0009] In some embodiments, the cyclic amine compound is selected from one or more of 3-aminophthalhydrazide, 3-amino-6-chloropyridazine, 1-aminoanthraquinone, 2-aminopyrimidine and 1-amino-4-methylpiperazine.

[0010] In some embodiments, in step S1, the molar ratio of the cyclic amine compound to the cobalt source is (3-10):1.

[0011] In some embodiments, in step S1, the cobalt source is selected from one or more of cobalt nitrate, cobalt chloride and cobalt acetate.

[0012] In some embodiments, in step S2, the mass ratio of the Co precursor to the copper source is (1:3) to (3:1).

[0013] In some embodiments, in step S2, the copper source is selected from one or more of copper nitrate, copper sulfate, copper chloride and copper acetate.

[0014] In some embodiments, in step S3, the temperature of the pyrolysis treatment is 500°C to 1000°C.

[0015] In some embodiments, in step S3, the pyrolysis treatment time is 1 h to 6 h.

[0016] In some embodiments, in step S4, the acid solution is selected from hydrochloric acid solution or sulfuric acid solution.

[0017] In some embodiments, in step S4, the concentration of the acid solution is 0.5 mol / L to 2 mol / L.

[0018] The third aspect of the present application provides a membrane electrode, which includes a catalyst layer, and the catalyst layer includes the catalyst provided in the first aspect or the catalyst prepared by the preparation method provided in the second aspect.

[0019] A fourth aspect of the present application provides a fuel cell, which includes the membrane electrode provided by the third aspect.

[0020] Compared with the traditional technology, this application has at least the following beneficial effects:

[0021] The catalyst provided in the present application has a carbon-nitrogen carrier with a nano-ordered pore structure, so that the active sites of the catalyst are fully exposed, the accessibility of the electrolyte is improved, and thus the activity and utilization rate of the catalyst are improved. The inner and outer surfaces of the carbon-nitrogen carrier are loaded with non-precious metal Co metal and Cu metal as catalytic particles, providing bimetallic active sites, which reduces the cost while making the catalyst have higher activity. When the catalyst is used in a fuel cell, it can catalyze the electrolysis of water and has a strong anti-reverse polarity ability, thereby improving the electrochemical performance and safety performance of the battery.

[0022] The preparation method of the catalyst provided in the present application is to chemically polymerize a cobalt source, a copper source and a cyclic amine compound and then perform a pyrolysis treatment and an acid treatment, so that the active metals Co and Cu are complexed on the surface of a carbon-nitrogen carrier in the form of particles, providing bimetallic active sites, and forming a nano-ordered pore structure on the carbon-nitrogen carrier, so that the active sites of the catalyst are fully exposed, and the accessibility of the electrolyte is improved, thereby improving the activity and utilization rate of the catalyst. When the formed Co / Cu-NC catalyst is used in a fuel cell, it can catalyze the electrolysis of water and has a strong anti-reverse polarity ability, thereby improving the electrochemical performance and safety performance of the battery; in addition, compared with the traditional preparation method, the preparation process of the catalyst in the present application is simple and the cost is low. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The figure is a schematic diagram of a process for preparing a catalyst in one embodiment. DETAILED DESCRIPTION

[0024] References to embodiments of the present application will now be provided in detail, one or more examples of which are described below. Each example is provided as an explanation rather than a limitation of the present application. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present application without departing from the scope or spirit of the present application. For example, a feature described or described as part of one embodiment may be used in another embodiment to produce a further embodiment.

[0025] Therefore, it is intended that the present application covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features and aspects of the present application are disclosed in or are apparent from the following detailed description. It will be appreciated by those of ordinary skill in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the present application.

[0026] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0027] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0028] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0029] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0030] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, it is mentioned that the method may also include step (c), which means that step (c) can be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0031] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0032] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0033] Terminology explanation:

[0034] "Nano ordered pore structure" means that the pore arrangement in the material is highly regular and repeatable, and the pore size is in the nanometer range (i.e., 1nm to 100nm).

[0035] "Cyclic amine compounds" refer to compounds in which at least one C atom on an aliphatic ring is replaced by a N atom.

[0036] The first aspect of the present application provides a catalyst, which includes a carbon-nitrogen carrier and catalytic particles. The carbon-nitrogen carrier has a nano-ordered pore structure. The catalytic particles are loaded on the carbon-nitrogen carrier, the catalytic particles include Co metal and Cu metal, and the catalytic particles and the carbon-nitrogen carrier form a Co / Cu-NC catalyst.

[0037] The catalyst provided in the present application has a carbon-nitrogen carrier with a nano-ordered pore structure, so that the active sites of the catalyst are fully exposed, the accessibility of the electrolyte is improved, and thus the activity and utilization rate of the catalyst are improved. The inner and outer surfaces of the carbon-nitrogen carrier are loaded with non-precious metal Co metal and Cu metal as catalytic particles, providing bimetallic active sites, which reduces the cost while making the catalyst have higher activity. When the catalyst is used in a fuel cell, it can catalyze the electrolysis of water and has a strong anti-reverse polarity ability, thereby improving the electrochemical performance and safety performance of the battery.

[0038] The second aspect of the present application provides a method for preparing a catalyst, such as Figure 1 As shown, the preparation method comprises the following steps:

[0039] S1. Dispersing a cyclic amine compound and a cobalt source in a solvent, stirring and reacting, and obtaining a Co precursor.

[0040] S2. Dispersing the Co precursor and the copper source in a solvent, stirring and reacting, to obtain a Co-Cu precursor.

[0041] S3. Pyrolyze the Co-Cu precursor to form powder.

[0042] S4. Acid solution is added to the powder for treatment, and then the powder is purified to obtain a Co / Cu-NC catalyst.

[0043] The preparation method of the catalyst provided in the present application is to chemically polymerize a cobalt source, a copper source and a cyclic amine compound and then perform a pyrolysis treatment and an acid treatment, so that the active metals Co and Cu are complexed on the surface of a carbon-nitrogen carrier in the form of particles, providing bimetallic active sites, and forming a nano-ordered pore structure on the carbon-nitrogen carrier, so that the active sites of the catalyst are fully exposed, and the accessibility of the electrolyte is improved, thereby improving the activity and utilization rate of the catalyst. When the formed Co / Cu-NC catalyst is used in a fuel cell, it can catalyze the electrolysis of water and has a strong anti-reverse polarity ability, thereby improving the electrochemical performance and safety performance of the battery; in addition, compared with the traditional preparation method, the preparation process of the catalyst in the present application is simple and the cost is low.

[0044] In some embodiments, in step S1, the cyclic amine compound is selected from one or more of 3-aminophthalhydrazide, 3-amino-6-chloropyridazine, pyrrole, 1-aminoanthraquinone, 2-aminopyrimidine and 1-amino-4-methylpiperazine.

[0045] Furthermore, the cyclic amine compound includes an amino group; the cyclic amine compound is selected from one or more of 3-aminophthalhydrazide, 3-amino-6-chloropyridazine, 1-aminoanthraquinone, 2-aminopyrimidine and 1-amino-4-methylpiperazine.

[0046] In some embodiments, in step S1, the molar ratio of the cyclic amine compound to the cobalt source is (3-10): 1. Exemplarily, the molar ratio of the cyclic amine compound to the cobalt source includes but is not limited to 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1.

[0047] In some embodiments, in step S1, the cobalt source is selected from one or more of cobalt nitrate, cobalt chloride and cobalt acetate.

[0048] In some embodiments, in step S1 or step S2, the solvent is ethanol or acetone.

[0049] In some implementation modes, step S1 specifically includes the following steps:

[0050] S11, dispersing the cyclic amine compound and the cobalt source in a solvent, stirring and reacting, to obtain a first mixed solution.

[0051] S12, centrifuging, washing and drying the first mixed solution in sequence to obtain a Co precursor.

[0052] In some embodiments, in step S11, the mass fraction of the first mixed solution is 20 g / L to 40 g / L. Exemplarily, the mass fraction of the first mixed solution includes but is not limited to 20 g / L, 25 g / L, 30 g / L, 35 g / L, and 40 g / L.

[0053] In some embodiments, in step S11, the stirring reaction is performed by mechanical stirring, and the stirring speed is 20 rpm to 50 rpm. For example, the stirring speed includes but is not limited to 20 rpm, 25 rpm, 30 rpm, 35 rpm, 40 rpm, 45 rpm, and 50 rpm.

[0054] In some embodiments, in step S11, the stirring reaction time is 6 hours to 16 hours. Exemplarily, the stirring reaction time includes but is not limited to 6 hours, 8 hours, 10 hours, 12 hours, 14 hours, and 16 hours.

[0055] In some embodiments, in step S12, the speed of the centrifuge during centrifugation is 1000 rpm to 3000 rpm. Exemplarily, the speed of the centrifuge includes but is not limited to 1000 rpm, 1500 rpm, 2000 rpm, 2500 rpm, and 3000 rpm.

[0056] In some embodiments, in step S2, the mass ratio of the Co precursor to the copper source is (1:3) to (3:1). Exemplarily, the mass ratio of the Co precursor to the copper source includes but is not limited to 1:3, 1:1, and 3:1.

[0057] In some embodiments, in step S12, the washing solvent is ethanol or distilled water.

[0058] In some embodiments, in step S12, the drying method is vacuum drying; the drying temperature is 40°C to 80°C, and the drying time is 8h to 16h. Exemplarily, the drying temperature includes but is not limited to 40°C, 50°C, 60°C, 70°C, and 80°C; the drying time includes but is not limited to 8h, 10h, 12h, 14h, and 16h.

[0059] In some embodiments, in step S2, the copper source is selected from one or more of copper nitrate, copper sulfate, copper chloride and copper acetate.

[0060] In some implementation modes, step S2 specifically includes the following steps:

[0061] S21, dispersing the Co precursor and the copper source in a solvent, stirring and reacting, to obtain a second mixed solution.

[0062] S22, centrifuging, washing and drying the second mixed liquid in sequence to obtain a Co-Cu precursor.

[0063] In some embodiments, in step S21, the stirring reaction is performed by mechanical stirring, and the stirring speed is 30 rpm to 60 rpm. Exemplarily, the stirring speed includes but is not limited to 30 rpm, 35 rpm, 40 rpm, 45 rpm, 50 rpm, 55 rpm, and 60 rpm.

[0064] In some embodiments, in step S21, the stirring reaction time is 12 hours to 24 hours. Exemplarily, the stirring reaction time includes but is not limited to 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours, and 24 hours.

[0065] In some embodiments, in step S22, the washing solvent is ethanol or distilled water.

[0066] In some embodiments, in step S22, the speed of the centrifuge during centrifugation is 2000 rpm to 5000 rpm. Exemplarily, the speed of the centrifuge includes but is not limited to 2000 rpm, 2500 rpm, 3000 rpm, 3500 rpm, 4000 rpm, 4500 rpm, and 5000 rpm.

[0067] In some embodiments, in step S22, the drying method is vacuum drying; the drying temperature is 40°C to 80°C, and the drying time is 8h to 16h. Exemplarily, the drying temperature includes but is not limited to 40°C, 50°C, 60°C, 70°C, and 80°C; the drying time includes but is not limited to 8h, 10h, 12h, 14h, and 16h.

[0068] In some embodiments, in step S3, the Co—Cu precursor is pyrolyzed in a tube furnace.

[0069] In some embodiments, in step S3, the temperature of the pyrolysis treatment is 500° C. to 1000° C. Exemplarily, the temperature of the pyrolysis treatment includes but is not limited to 500° C., 600° C., 700° C., 800° C., 900° C., and 1000° C. Within the above temperature range of the pyrolysis treatment, the catalyst carrier is ensured to be fully formed, so that the active sites of the catalyst are fully exposed, while reducing the agglomeration of metal particles.

[0070] In some embodiments, in step S3, the pyrolysis treatment time is 1 hour to 6 hours. Exemplarily, the pyrolysis treatment time includes but is not limited to 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, and 6 hours.

[0071] In some embodiments, in step S3, the pyrolysis treatment is performed under the protection of an inert gas; the inert gas is one of nitrogen, argon or helium.

[0072] In some embodiments, in step S4, the acid solution is selected from hydrochloric acid solution or sulfuric acid solution.

[0073] In some embodiments, in step S4, the concentration of the acid solution is 0.5 mol / L to 2 mol / L. Exemplarily, the concentration of the acid solution includes but is not limited to 0.5 mol / L, 1 mol / L, 1.5 mol / L, and 2 mol / L.

[0074] In some implementation modes, step S4 specifically includes the following steps:

[0075] S41. Add acid solution to the powder and stir.

[0076] S42, filtering, washing and drying are performed in sequence to obtain a Co / Cu-NC catalyst.

[0077] In some embodiments, in step S41, the stirring method is mechanical stirring, the stirring speed is 10rpm to 40rpm, and the stirring time is 4h to 8h. Exemplarily, the stirring speed includes but is not limited to 10rpm, 15rpm, 20rpm, 25rpm, 30rpm, 35rpm, 40rpm; the stirring time includes but is not limited to 4h, 5h, 6h, 7h, 8h.

[0078] In some embodiments, in step S42, filtering is performed using a filter membrane; further, the filter membrane is an ultrafiltration membrane, and the pore size of the ultrafiltration membrane is 100nm to 1000nm. Exemplarily, the pore size of the ultrafiltration membrane is 100nm, 200nm, 400nm, 600nm, 800nm, and 1000nm.

[0079] In some embodiments, in step S42, the washing solvent is ethanol or distilled water.

[0080] In some embodiments, in step S42, the drying method is vacuum drying; the drying temperature is 60°C to 80°C, and the drying time is 8h to 12h. Exemplarily, the drying temperature includes but is not limited to 60°C, 70°C, and 80°C; the drying time includes but is not limited to 8h, 9h, 10h, 11h, and 12h.

[0081] The third aspect of the present application provides a membrane electrode, which includes a catalyst layer, and the catalyst layer includes the catalyst provided in the first aspect or the catalyst prepared by the preparation method provided in the second aspect.

[0082] A fourth aspect of the present application provides a fuel cell, which includes the membrane electrode provided by the third aspect.

[0083] The present application will be further described below with reference to specific embodiments and comparative examples.

[0084] Example 1

[0085] This embodiment provides a catalyst and a preparation method thereof.

[0086] (1) 8 g of 3-amino-6-chloropyridazine and 3 g of cobalt nitrate were dispersed in 300 mL of ethanol, and the mixture was reacted for 12 h under mechanical stirring at 30 rpm to obtain a first mixed solution; wherein the molar ratio of 3-amino-6-chloropyridazine to cobalt nitrate was 6:1.

[0087] (2) The first mixed solution was centrifuged at a speed of 2000 rpm to obtain a solid, which was washed with ethanol three times and then placed in a vacuum drying oven and dried at 65° C. for 8 h to obtain a Co precursor.

[0088] (3) Dispersing 3 g of Co precursor and 1 g of copper nitrate in 150 mL of ethanol, stirring at 40 rpm for 16 h, and obtaining a second mixed solution; wherein the mass ratio of the Co precursor to the copper nitrate is 3:1.

[0089] (4) The second mixed solution was centrifuged at 2000 rpm to obtain a solid, which was washed three times with ethanol and placed in a vacuum drying oven at 60° C. for 12 h to obtain a Co-Cu precursor.

[0090] (5) The Co-Cu precursor was placed in a tube furnace and pyrolyzed at 800 °C for 2 h under nitrogen protection to obtain a powder.

[0091] (6) The powder was transferred to a round-bottom flask, 150 mL of 1 mol / L sulfuric acid was added, and the mixture was stirred at 20 rpm for 5 h. The solid was then filtered using a 600 nm ultrafiltration membrane. After washing with ethanol three times, the solid was placed in a vacuum oven and dried at 65 °C for 10 h to obtain a Co / Cu-NC catalyst.

[0092] Example 2

[0093] The catalyst and preparation method provided in this embodiment are basically the same as those in embodiment 1, except that:

[0094] In step (1), 8 g of 3-amino-6-chloropyridazine and 3 g of cobalt nitrate are replaced by 7 g of 2-aminopyrimidine and 3.5 g of cobalt acetate; wherein the molar ratio of 2-aminopyrimidine to cobalt nitrate is 3.5:1.

[0095] In step (3), 3 g of Co precursor and 1 g of copper nitrate are replaced with 2 g of Co precursor and 2 g of copper nitrate; wherein the mass ratio of Co precursor to copper nitrate is 1:1.

[0096] Example 3

[0097] The catalyst and preparation method provided in this embodiment are basically the same as those in embodiment 1, except that:

[0098] In step (1), 8 g of 3-amino-6-chloropyridazine and 3 g of cobalt nitrate are replaced by 6.2 g of pyrrole and 3 g of cobalt chloride; wherein the molar ratio of pyrrole to cobalt chloride is 4:1.

[0099] In step (3), 3 g of Co precursor and 1 g of copper nitrate are replaced by 2 g of Co precursor and 3 g of copper chloride; wherein the mass ratio of Co precursor to copper chloride is 2:3.

[0100] Example 4

[0101] The catalyst and preparation method provided in this embodiment are basically the same as those in embodiment 1, except that:

[0102] In step (5), the temperature of the pyrolysis treatment is 1000°C.

[0103] Example 5

[0104] The catalyst and preparation method provided in this embodiment are basically the same as those in embodiment 1, except that:

[0105] In step (5), the temperature of the pyrolysis treatment is 500°C.

[0106] Comparative Example 1

[0107] This comparative example provides a catalyst and a preparation method thereof.

[0108] (1) 8 g of 3-amino-6-chloropyridazine and 3 g of cobalt nitrate were dispersed in 300 mL of ethanol, and the mixture was reacted for 12 h under mechanical stirring at 30 rpm to obtain a first mixed solution; wherein the molar ratio of 3-amino-6-chloropyridazine to cobalt nitrate was 6:1.

[0109] (2) The first mixed solution was centrifuged at a speed of 2000 rpm to obtain a solid, which was washed with ethanol three times and then placed in a vacuum drying oven and dried at 65° C. for 8 h to obtain a Co precursor.

[0110] (3) The Co precursor was placed in a tube furnace and pyrolyzed at 800 °C for 2 h under nitrogen protection to obtain a powder.

[0111] (4) The powder was transferred to a round-bottom flask, 150 mL of 1 mol / L sulfuric acid was added, and the mixture was stirred at 20 rpm for 5 h. The solid was then filtered using a 600 nm ultrafiltration membrane. After washing with ethanol three times, the solid was placed in a vacuum oven and dried at 65 °C for 10 h to obtain a Co-NC catalyst.

[0112] Comparative Example 2

[0113] This comparative example provides a catalyst and a preparation method thereof.

[0114] (1) 8 g of 3-amino-6-chloropyridazine and 1.3 g of copper nitrate were dispersed in 300 mL of ethanol, and the mixture was reacted for 12 h under mechanical stirring at 30 rpm to obtain a first mixed solution; wherein the molar ratio of 3-amino-6-chloropyridazine to cobalt nitrate was 6:1.

[0115] (2) The first mixed solution was centrifuged at a speed of 2000 rpm to obtain a solid, which was washed with ethanol three times and then placed in a vacuum drying oven and dried at 65° C. for 8 h to obtain a Cu precursor.

[0116] (3) The Cu precursor was placed in a tube furnace and pyrolyzed at 800 °C for 2 h under nitrogen protection to obtain a powder.

[0117] (4) The powder was transferred to a round-bottom flask, 150 mL of 1 mol / L sulfuric acid was added, and the mixture was stirred at 20 rpm for 5 h. The solid was then filtered using a 600 nm ultrafiltration membrane. The solid was washed three times with ethanol and then placed in a vacuum oven and dried at 65 °C for 10 h to obtain a Cu-NC catalyst.

[0118] Performance Testing

[0119] (1) Half-cell test

[0120] The catalysts obtained in the embodiments and comparative examples were subjected to electrochemical tests on a half-cell. The specific method is as follows: weigh an appropriate amount of the catalysts obtained in the embodiments and comparative examples, add an appropriate amount of deionized water thereto, then add isopropanol and Nafion D520 solution, and ultrasonicate until the catalyst slurry is evenly mixed. Take 10 μL of the slurry and drop it on the electrode surface of the standard electrode. After drying at room temperature, it is used as the working electrode. A platinum wire is used as the counter electrode, a reversible hydrogen electrode is used as the reference electrode, and a 0.5 mol / L nitrogen-saturated sulfuric acid solution is used as the electrolyte to construct a 3.4-mm electrolytic cell. The polarization test is carried out at a rotation speed of 1600 rpm and a scan rate of 5 mV / s. The test results are shown in Table 1.

[0121] Table 1

[0122] Starting potential (V) <![CDATA[Overpotential @ 10 mA / cm 2 (mV)]]> Example 1 1.39 295 Example 2 1.40 298 Example 3 1.42 309 Example 4 1.41 303 Example 5 1.42 313 Comparative Example 1 1.45 365 Comparative Example 2 1.43 342

[0123] As shown in Table 1, by comparing Examples 1 to 5 with Comparative Examples 1 to 2, it can be seen that by chemically polymerizing Co metal and Cu metal with cyclic amine compounds and pyrolyzing to obtain a dual-active metal anti-reverse polarity catalyst, it has a smaller starting potential and overpotential, and has a better anti-reverse polarity ability; the active metal of the anti-reverse polarity catalyst is complexed on the surface of the carbon nitrogen carrier in the form of nanoparticles, fully exposing the active sites, improving the accessibility of the electrolyte, and improving the activity and utilization of the catalyst. In Comparative Examples 1 and 2, Co or Cu single metal is complexed on the carbon nitrogen carrier, and the activity of the anti-reverse polarity catalyst decreases due to the reduction of active sites.

[0124] As shown in Table 1, by comparing Examples 1, 4, and 5, it can be seen that the pyrolysis temperature of the precursor will affect the performance of the catalyst. If the pyrolysis temperature is too high, the thermal motion of the metal ions will be enhanced, the metal agglomeration ability will increase, and the active sites of the catalyst will be reduced; if the pyrolysis temperature is too low, the catalyst carrier cannot be fully formed, and the active sites of the catalyst cannot be fully exposed. In order to obtain a catalyst with better performance, the pyrolysis temperature of the precursor needs to be controlled at 500°C to 1000°C.

[0125] (2) Single battery test

[0126] An appropriate amount of Pt / C catalyst was added to the slurry of the catalyst obtained in each embodiment and comparative example and further ultrasonically mixed to prepare a catalyst slurry, a CCM with the same precious metal loading was prepared by a conventional ultrasonic spraying method, and a membrane electrode (MEA) was prepared using the same materials and process conditions, and the performance test and anti-reverse polarity test of the catalyst obtained in each embodiment and comparative example were tested in a single cell.

[0127] The single cell test conditions are: the effective area of ​​the single cell is 5×5cm 2 , temperature 80℃; anode relative humidity 100%RH, cathode relative humidity 100%RH, anode and cathode gas pressure 150kPa. After the fuel cell is activated and the IV polarization test is completed, connect an external 0.2A / cm 2 A constant current source with a current density of 2 / Air state until the voltage is stable. Then switch the anode H2 to N2 to simulate the working condition of reverse polarity caused by insufficient anode H2. Set -1.5V as the cut-off voltage. When the battery voltage is lower than -1.5V, the constant current source stops working, that is, the reverse polarity ends. The voltage starts to drop sharply until the reverse polarity ends. The time is considered as the anti-reverse polarity time. The test results are shown in Table 2.

[0128] Table 2

[0129]

[0130] As shown in Table 2, at the same catalyst loading, the single shutdown anti-reverse time of the membrane electrode prepared with the catalyst obtained in Examples 1 to 5 is much longer than that of Comparative Examples 1 to 2, which shows that the catalyst prepared by the preparation method of the present application has a strong anti-reverse ability. Comparing the loss of membrane electrode performance before and after the reversal, after one shutdown for reversal, the battery performance in Example 1 remained basically unchanged, and the battery performance in Examples 2 to 5 only showed a slight decrease. The battery performance of Comparative Examples 1 and 2 decayed sharply, which is mainly because the local carbon carrier material was corroded by the reversal, resulting in uneven distribution of active components in the anode catalyst layer, causing Pt agglomeration or loss, resulting in a decrease in electrochemical performance.

[0131] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0132] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A catalyst, characterized in that include: Carbon-nitrogen carrier with nano-ordered pore structure; as well as Catalytic particles are loaded on the carbon-nitrogen carrier, the catalytic particles include Co metal and Cu metal, and the catalytic particles and the carbon-nitrogen carrier form a Co / Cu-NC catalyst.

2. A method for preparing a catalyst, characterized in that: The following steps are involved: S1, dispersing a cyclic amine compound and a cobalt source in a solvent, stirring and reacting to obtain a Co precursor; S2, dispersing the Co precursor and the copper source in a solvent, stirring and reacting to obtain a Co-Cu precursor; S3, pyrolyzing the Co-Cu precursor to form powder; S4, adding acid solution to the powder for treatment, and then purifying it to obtain a Co / Cu-NC catalyst.

3. The method for preparing the catalyst according to claim 2, characterized in that: In step S1, the cyclic amine compound includes an amino group.

4. The method for preparing the catalyst according to claim 3, characterized in that: The cyclic amine compound is selected from one or more of 3-aminophthalhydrazide, 3-amino-6-chloropyridazine, 1-aminoanthraquinone, 2-aminopyrimidine and 1-amino-4-methylpiperazine.

5. The method for preparing a catalyst according to any one of claims 2 to 4, characterized in that: In step S1, the molar ratio of the cyclic amine compound to the cobalt source is (3-10):1; and / or, The cobalt source is selected from one or more of cobalt nitrate, cobalt chloride and cobalt acetate.

6. The method for preparing a catalyst according to any one of claims 2 to 4, characterized in that: In step S2, the mass ratio of the Co precursor to the copper source is (1:3) to (3:1); and / or, The copper source is selected from one or more of copper nitrate, copper sulfate, copper chloride and copper acetate.

7. The method for preparing a catalyst according to any one of claims 2 to 4, characterized in that: In step S3, the temperature of the pyrolysis treatment is 500° C. to 1000° C.; and / or, The pyrolysis treatment time is 1 h to 6 h.

8. The method for preparing a catalyst according to any one of claims 2 to 4, characterized in that: In step S4, the acid solution is selected from hydrochloric acid solution or sulfuric acid solution; and / or, The concentration of the acid solution is 0.5 mol / L to 2 mol / L.

9. A membrane electrode, characterized in that: The catalyst layer comprises the catalyst according to claim 1 or the catalyst prepared by the preparation method according to any one of claims 2 to 8.

10. A fuel cell, characterized in that: Comprising the membrane electrode according to claim 9.